INTERNATIONAL MIGRATION PROCESSES IN THE CONTEXT OF MILITARY CONFLICTS AS A FACTOR OF GLOBAL ECONOMIC DEVELOPMENT TRANSFORMATION (INNOVATIVE ECONOMY, 2024)
Herman L.T., Karas O.S. INTERNATIONAL MIGRATION PROCESSES IN THE CONTEXT OF MILITARY CONFLICTS AS A FACTOR OF GLOBAL ECONOMIC DEVELOPMENT TRANSFORMATIONPurpose. The aim of the article is to analyse the impact of international migration processes on global economic development in the context of armed conflicts.Methodology of research. The following research methods were employed to achieve the set goal: statistical data analysis (utilizing statistical data on migration flows, armed conflicts, and economic indicators to identify correlations and trends in their interrelation); documentary analysis (investigating official documents, reports from international organizations, scientific publications, and other sources to gather information about armed conflicts, migration flows, and their implications for the economy); case studies (conducting in-depth analyses of specific migration cases resulting from armed conflicts and their impact on the economic situation in both origin and destination countries).Findings. The problems of the development of migration processes and their regularities are summarized. The state of migration processes related to military conflicts is analysed. The advantages and disadvantages of forced migration for host countries and countries of origin of migrants are systematized. The integration of refugees into the environment of the host country was monitored and the challenges associated with this process were analysed. The regularities of the impact of migration processes caused by military conflicts on the transformation of global economic development have been revealed. Peculiarities of modern migration processes in Ukraine are studied.Originality. The scientific novelty of the research lies in the detailed analysis of the relationships between migration flows and armed conflicts and their impact on global economic development. Current situations and conflicts are analyzed, allowing for fresh data and conclusions regarding their influence on migration and the economy.Practical value. The substantiated results of the study of international migration processes in the context of military conflicts can have a significant practical impact on the development of policies, programmes and strategies at both the country and international levels.Key words: migration, migration processes, global economy, economic development, forced migration, refugee, host country.
Keywords: migration; migration processes; global economy; economic development; forced migration; refugee; host country.